Steering towards collaborative assessment: a qualitative study of parents' experiences of evidence-based assessment practices for their child with cerebral palsy. Issue 4 (13th February 2021) - O'Connor, Bridget; Kerr, Claire; Shields, Nora; Adair, Brooke; Imms, Christine
Abstract: Purpose: To understand parents' experiences of evidence-based assessment by health professionals for their child with cerebral palsy. Methods: A qualitative interpretive description study was undertaken. Primary carers of children with cerebral palsy (aged 3–18 years) from south-eastern Australia were invited to participate. Face-to-face interviews were held using a semi-structured topic guide and data analyzed inductively. Credibility was ensured through: journal reflections; co-author review; audit trail; and, participant member-checking. Results: Fourteen parents of children with cerebral palsy, representing Gross Motor Functional Classification System levels I–V, participated. Six themes emerged: (1) Protection; (2) Positively Framed; (3) Bridging the Gap; (4) Involvement; (5) Finding Worth; and (6) Trust. Central to parents' experience was protection of their child's identity and personal self. Assessment can be emotionally confronting, at any stage. Representing the child positively and highlighting possibilities was deemed essential. Parents' involvement ranged from being overlooked spectators to being instigators of assessment. Evidence-based assessment was worthwhile when relevant to parents' direction and family context. The researchers' interpretive description generated a schema and metaphor—the Steering Wheel for Collaborative Assessment. Conclusions: A strengths-based approach to diagnosis and assessment is essential. The resulting interpretive description may assist health professionals align evidence-based assessment practices with family-centred care. Implications for rehabilitation: Parents of children who have cerebral palsy describe having to protect their child's identity and representation, and their own personal well-being, through evidence-based assessment and diagnostic processes. Involving parents in the process of evidence-based assessment and adopting a strengths-based approach is essential. The interpretive description developed—the Steering Wheel for Collaborative Assessment—may assist health professionals to implement evidence-based assessment tools in ways consistent with family-centred care principles.